2016
DOI: 10.1111/nph.13829
|View full text |Cite
|
Sign up to set email alerts
|

Seedling root responses to soil moisture and the identification of a belowground trait spectrum across three growth forms

Abstract: SummaryRoot trait variation and plasticity could be key factors differentiating plant performance under drought. However, water manipulation and root measurements are rarely coupled empirically across growth forms to identify whether belowground strategies are generalizable across species.We measured seedling root traits across three moisture levels in 18 Mediterranean forbs, grasses, and woody species.Drought increased the root mass fraction (RMF) and decreased the relative proportion of thin roots (indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 74 publications
(148 reference statements)
9
88
5
Order By: Relevance
“…Williams & Black ; Padilla et al . ; Drenovsky, Khasanova & James ; Larson & Funk ). Several of these responses (rapid elongation, high SRL) are contrary to strategies found in species adapted to low rainfall environments (Wright & Westoby ; Nicotra, Babicka & Westoby ).…”
Section: Discussionmentioning
confidence: 99%
“…Williams & Black ; Padilla et al . ; Drenovsky, Khasanova & James ; Larson & Funk ). Several of these responses (rapid elongation, high SRL) are contrary to strategies found in species adapted to low rainfall environments (Wright & Westoby ; Nicotra, Babicka & Westoby ).…”
Section: Discussionmentioning
confidence: 99%
“…Root traits are notoriously difficult to measure, although there is some evidence that an economic axis for roots exists as well, with slow-growing species having low root elongation rates, low specific root length (SRL), high root diameter, and low nutrient concentration Liu et al, 2010;Larson & Funk, 2016). In arid and semi-arid ecosystems, responses to changes in water availability may be better predicted from root traits such as root depth or elongation rate than from leaf traits (Nicotra, Babicka & Westoby, 2002;Padilla & Pugnaire, 2007).…”
Section: (A) Response Traitsmentioning
confidence: 99%
“…phenotypic plasticity, see Section III), which contributes to functional variation within communities (e.g. Funk, 2008;Ashton et al, 2010;Firn et al, 2012;SiebenkĂ€s, Schumacher & Roscher, 2015;Larson & Funk, 2016). Although empirical links between phenotypic plasticity and performance or fitness are still rare across species (van Kleunen & Fischer, 2005;Firn et al, 2012), if plasticity is adaptive it could be an important metric related to population, species, and community responses to environmental change (reviewed in Berg & Ellers, 2010;Nicotra et al, 2010;Valladares et al, 2014).…”
Section: (A) Response Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies testing for the presence of a RES across species have produced mixed results. For example, recent studies have found evidence for a RES in herbaceous species, but analyses suggest woody species show drastically different patterns (Larson and Funk, 2016; Roumet et al, 2016; Weemstra et al, 2016). …”
Section: Introductionmentioning
confidence: 99%